Malaysia’s response to the Cambodian conflict, 1978-1991 - Dunita Nabila A. Rahimin; Wong, Danny Tze Ken (Penerbit UKM, 2025)
In late 1978, Vietnam began its invasion in Cambodia, resulted in the overthrowing of the Khmer Rouge regime which was responsible for the Cambodian Genocide. This invasion resulting in the establishment of the People’s Republic of Kampuchea, backed by Vietnam, while the Khmer Rouge and other factions continued to resist. Throughout the 1980s, Cambodia remained embroiled in civil war, with factions, including the Khmer Rouge, fighting the Vietnamese-backed government. The invasion also led to border clashes along Thailand’s border, positioning Thailand as a frontline state in the Cambodian Conflict, drawing the attention of neighbouring countries like Malaysia. As the conflict escalated and threatened Thai sovereignty, Malaysia’s stance on the issue began to take shape. This raises two key questions: To what extent did Thailand’s position influence Malaysia’s attitude? What were Malaysia’s attitudes during the conflict? By analysing Malaysia’s responses under Prime Ministers Hussein Onn and Mahathir Mohamad, this article examines Malaysia’s foreign policies towards Indochina, its objectives in seeking a resolution, and how the conflict shaped its attitudes. The study uses qualitative research, drawing from archival documents at The National Archives in Kew and the National Archives of Malaysia, alongside newspapers, books, theses, and journal articles. Under Hussein Onn, Malaysia focused on direct security concerns, particularly regarding Thailand’s position in the conflict. In contrast, Mahathir Mohamad’s leadership recognised the indirect security implications of Thailand’s position, framing them within a broader regional context. Malaysia’s response under Mahathir sought to facilitate ASEAN cooperation to address security challenges while balancing national and regional interests.